2012
DOI: 10.2147/ijn.s37075
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm properties of yttrium fluoride nanoparticles

Abstract: Antibiotic resistance has prompted the search for new agents that can inhibit bacterial growth. Moreover, colonization of abiotic surfaces by microorganisms and the formation of biofilms is a major cause of infections associated with medical implants, resulting in prolonged hospitalization periods and patient mortality. In this study we describe a water-based synthesis of yttrium fluoride (YF 3 ) nanoparticles (NPs) using sonochemistry. The sonochemical irradiation of an aqueous solution of yttrium (III) aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Biofilm formation with nanoparticles is prevented by designing the surfaces to prevent limited bacterial colonization. 17 Bacterial attachment and biofilm formation is inhibited by coating, impregnation, or embossing nanomaterial surfaces by nano-functionalization. 17 Thus, nanoparticles have emerged as a new field of struggle against biofilms.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation with nanoparticles is prevented by designing the surfaces to prevent limited bacterial colonization. 17 Bacterial attachment and biofilm formation is inhibited by coating, impregnation, or embossing nanomaterial surfaces by nano-functionalization. 17 Thus, nanoparticles have emerged as a new field of struggle against biofilms.…”
Section: Review Articlementioning
confidence: 99%
“…17 Bacterial attachment and biofilm formation is inhibited by coating, impregnation, or embossing nanomaterial surfaces by nano-functionalization. 17 Thus, nanoparticles have emerged as a new field of struggle against biofilms. 18 There are several studies on the antimicrobial and antibiotic activities of silver nanoparticles, and it has been reported that such nanomaterials can be used in the production of medical biomaterials.…”
Section: Review Articlementioning
confidence: 99%
“…aeruginosa, Serratia marcescens Inhibition of bacterial growthKannan and Sundrarajan (2015), Lee et al (2018)YF 3 E . coli , S. aureus Reduction of bacterial colonization on YF 3 coated-surface and antibiofilm activitiesLellouche et al (2012a, b), Hemeg (2017)CdS E . coli Antibiofilm activityDhanabalan and Gurunathan (2015), Hemeg (2017)MgF 2 E .…”
Section: Introductionmentioning
confidence: 99%
“…coli , S . aureus Inhibition of biofilm formation; ROS generation, lipid peroxidation and penetration of cell envelopeLellouche et al (2012a, b), Hemeg (2017)Bi S . mutans Reduction of bacterial growth; inhibition of biofilm formationHernandez-Delgadillo et al (2012), Hemeg (2017) NPs nanoparticles, ROS reactive oxygen species…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium NCs can be applied in drug release and targeted cancer cell ablation (Xu et al 2012 ). The YF(3) NC-coated catheters were able to significantly reduce bacterial colonization (Lellouche et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%